Intragenic Complementation Between Temperature-Sensitive Mutants of Gene 42 (dCMP Hydroxymethylase) of Bacteriophage T4 - Chiu, Che-Shen (1973)
Interallelic complementation between certain temperature-sensitive mutants of gene 42 of bacteriophage T4 was demonstrated by measuring the incorporation of labeled thymine into DNA.